P85 Virtual lung cancer clinic: early experience and feasibility. (15th November 2016) - Faccenda, JF; Calvert, LD; Brij, SO
Abstract : Background: With increased public awareness, cough campaigns and incidental nodules on computed tomography (CT), referrals on a Lung Cancer Pathway (LC) have risen significantly. Safe and effective methods to transfer patients to Respiratory Pathways (RP) are essential. Aims: to evaluate a chose and book, virtual Lung Cancer Clinic (VLCC) to facilitate non-face-to-face "blind" rapid patient assessment, next investigation and appropriate out-patient review. Methods: A retrospective review of all referrals during the period March–May 2016 was undertaken to assess whether blind clinical decision-making at point of referral was sufficient to plan on-going management. Results: 60 referrals were reviewed in VLCC by a Lung Cancer Consultant Physician (average time from referral 2 days, range 0–4 days) as their first 2 week wait appointment. 17 (28%) patients had a final diagnosis of Lung Cancer (histological 12, radiological 5). Only 29/60 (48%) were of an acceptable quality for blind decision making. 16 (27%) referrals did not have sufficient information provided to allow any decision to be made and further information from the GP was requested. 26 referrals (43%) were removed from CP onto RP at VLCC review: 14 did not require a CT; 12 scans were undertaken (7 high resolution CT, 1 CT pulmonary angiogram, 4 staging CT), 8 prior to clinic attendance. 34 referrals (57%) remained on CP: 30 (88%) proceeded to staging CT with average wait 12 days (range 3–17 days) from referral, all performed prior to clinic attendance. 1/34 died prior to clinic attendance. 3/34 were scanned before VLCC. A further 8 referrals were removed from CP after imaging. Thus, only 36/60 (60%) referrals were seen in the Lung Cancer Clinic. There was appropriate pathway change in 30% of referrals to General Respiratory (25%) and Pleural Clinic (5%). Conclusion: The VLCC can effectively assess and plan next investigation with appropriate clinic follow-up for suspected Lung Cancer patients. However, blind decision-making relies upon good clinical information from the referrer and administrative time can be wasted chasing this. Our data confirms that the VLCC facilitates efficient use of Out-patient and Radiology Services.